MATLAB and VHDL model of real time partial discharge detection using FPGA technology - Emilliano; Chakrabarty C.K.; Ramasamy A.K.; Ghani A.B.A. (2023)
This research involves evaluating the use of FPGA for the detection and counting of partial discharge (PD) signals in underground cables (XLPE cables). PD detection model was designed one using MATLAB and another using VHDL. The pulse signal from the cable was processed and counted using peak detector and FPGA technology. The peak detector placed inside the VHDL program when the program of PD detection model was designed using VHDL program. Then, the model designed was used for testing and validation. Both models are able detect the PD signals and the results obtained are similar. 2011 IEEE.